Pengaruh pemanfaatan limbah batu pipih umeanyar sebagai subtitusi sebagian agregat halus terhadap kuat tekan dan kuat tarik belah beton - Ni Kadek Astariani; I Gusti Ngurah Eka Partama; I Wayan Eka Ariantika (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Concrete is a building material that is currently widely used in the construction sector. The increasing demand for concrete materials will cause the availability of materials taken from nature to decrease. Therefore, alternatives are needed to find substitutes for these natural materials, one of which is by using slate stone waste as a substitute for fine aggregate (sand). To increase the economic value of waste produced from the stone crushing industry, research was carried out using slate stone waste as a substitute for fine aggregate in normal concrete mixtures. By substituting some of the fine aggregate with slate stone waste, it is hoped that it can increase the compressive strength and split tensile strength of the concrete. Test specimens with a cylindrical shape with dimensions of 150mm x 300mm were made in a total of 80 pieces and tested at the age of 7 days and 28 days with a variety of test objects, namely normal concrete as a control (BN), fine aggregate substitution 25% (BP25%), 50% (BP50%), 75% (BP75%), 100% (BP100%). The optimum compressive strength value obtained was 36.91 MPa with fine aggregate substitution of 57.02%. This compressive strength value is 23.24% greater than normal concrete. Meanwhile, the optimum splitting tensile strength value is 2.42 MPa, with fine aggregate substitution of 46.15%. This tensile strength value is 9.01% greater than normal concrete. With the results of compressive strength and splitting tensile strength being greater than normal concrete, slate stone waste can be recommended as a partial substitute for fine aggregate.